Desempenho térmico de coberturas: Um estudo comparativo entre as telhas de material reciclado, de fibra e betume, fibrocimento e cerâmica - Jardim, Patricia Rafaella Salgado Abreu (2011)
This study aims to compare the thermal performance of tiles made from recycled material (waste packaging cardboard with aluminized film) with the tiles of fiber and bitumen, fiber cement and red ceramic with the aim of verifying the suitability of tile to be used in hot and humid climate of low latitude. The samples were selected according to the availability from Natal - RN market, as they are sold to the consumers. The methodology was based on studies that used experimental apparatus composed of thermal chambers heated by banks of incandescent bulbs, to analyze the thermal performance of materials. The tiles in the study were submitted to analysis of thermal performance, thermophysical properties and absorptance, using chambers of thermal performance, measuring the thermophysical properties and portable spectrometer, respectively. Comparative analysis of thermal performance between two samples of the recycled material with dimple sizes and different amounts of aluminum were made, in order to verify, if these characteristics had some interference on the thermal performance of them; the results showed no significant performance differences between the samples. The data obtained in chambers of thermal performance and confirmed by statistical analysis, showed, that the tile of recycled material have similar thermal performance to the tile of fiber cement. In addition to these tests was carried out the automatic monitoring of a building covered with tiles of recycled material, to verify its thermal performance in a real situation. The results showed that recycled shingles must be used with technical criteria similar to those used for fiber cement tiles, with regard to the heat gain into the building. Within these criteria should be taken into account local characteristics, especially in regions with hot and humid climate, and its use must be associated, according to the literature, to elements of thermal insulation and use of passive techniques such as vented attics, ceilings and right foot higher